Transport behaviours among older teenagers from semi‐rural New Zealand. (4th July 2018) - Ward, Aimee L.; McGee, Rob; Freeman, Claire; Gendall, Philip J.; Cameron, Claire
Abstract: Objective : Transport impacts teenagers by affecting their autonomy and independent access to activities. This manuscript reports descriptive findings of transport behaviours among teenagers in Southland, New Zealand, and discusses the implications of these for public health and policy. Methods : An online survey was implemented to investigate transport among respondents aged 16 years and older from twelve secondary schools. Two methods of survey distribution were used (in‐class and at home). Descriptive results were analysed using Stata. Results : Response rate was 71.5% (n=775). The most common forms of transport were as a passenger in a car and walking. Two‐thirds of participants had some form of driving licence. Half the sample expressed frustration at being unable to access activities. Significant gender differences existed regarding transport and types of activities accessed. Licence status was associated with physical activity, screen time and transport frustration. Conclusions : The transport decisions made by teenagers, in aggregate, have implications for policy and infrastructure, and findings provide a foundation for discussions around potential changes to driver education programming, the school uniform policy in New Zealand and further research. Implications for public health : Inquiring about everyday transport habits, outside of the trip to school, and activities accessed provided data about an under‐researched group, supporting the ecological approach to transport in the context of public health.